Melia Azedarach L. And Caesalpinia Gillesii Wall Plant Generative Propagation Methods - Jalolov Komiljon Baxromovich; To‘ychiev Xikmatullo Yuldashalievich (Scientific Trends, 2023)
Methods of generative reproduction of Melia azedarach L. and Caesalpinia gillesii Wall plants are studied in the article. Also, the morphometry of plant seeds, planting dates, the height of annual branches, the diameter of the root neck, bluishness, the preservation of seedlings, the dynamics of growth of branches, and the compliance of seedlings with the requirements of UzDst level has been studied.
Keywords: Melia azedarach L., Caesalpinia gillesii Wall, generative organ, seed, seedling, stem growth dynamics.